Gold Nanomaterials and Bone/Cartilage Tissue Engineering: Biomedical Applications and Molecular Mechanisms - Shi, Yifeng; Han, Xuyao; Pan, Shuang; Wu, Yuhao; Jiang, Yuhan; Lin, Jinghao; Chen, Yihuang; Jin, Haiming (Frontiers in Chemistry, 2021)
Recently, as our population increasingly ages with more pressure on bone and cartilage diseases, bone/cartilage tissue engineering (TE) have emerged as a potential alternative therapeutic technique accompanied by the rapid development of materials science and engineering. The key part to fulfill the goal of reconstructing impaired or damaged tissues lies in the rational design and synthesis of therapeutic agents in TE. Gold nanomaterials, especially gold nanoparticles (AuNPs), have shown the fascinating feasibility to treat a wide variety of diseases due to their excellent characteristics such as easy synthesis, controllable size, specific surface plasmon resonance and superior biocompatibility. Therefore, the comprehensive applications of gold nanomaterials in bone and cartilage TE have attracted enormous attention. This review will focus on the biomedical applications and molecular mechanism of gold nanomaterials in bone and cartilage TE. In addition, the types and cellular uptake process of gold nanomaterials are highlighted. Finally, the current challenges and future directions are indicated.